The AhR‐SRC axis as a therapeutic vulnerability in BRAFi‐resistant melanoma - Anaïs Paris; Nina Tardif; Francesca M Baietti; Cyrille Berra; Héloïse M Leclair; Eleonora Leucci; Marie‐Dominique Galibert; Sébastien Corre (EMBO Molecular Medicine)
Abstract The nongenetic mechanisms required to control tumor phenotypic plasticity and shape drug‐resistance remain unclear. We show here that the Aryl hydrocarbon Receptor (AhR) transcription factor directly regulates the gene expression program associated with the acquisition of resistance to BRAF inhibitor (BRAFi) in melanoma. In addition, we show in melanoma cells that canonical activation of AhR mediates the activation of the SRC pathway and promotes the acquisition of an invasive and aggressive resistant phenotype to front‐line BRAFi treatment in melanoma. This nongenetic reprogramming identifies a clinically compatible approach to reverse BRAFi resistance in melanoma. Using a preclinical BRAFi‐resistant PDX melanoma model, we demonstrate that SRC inhibition with dasatinib significantly re‐sensitizes melanoma cells to BRAFi. Together we identify the AhR/SRC axis as a new therapeutic vulnerability to trigger resistance and warrant the introduction of SRC inhibitors during the course of the treatment in combination with front‐line therapeutics to delay BRAFi resistance.